Youth perspective on social media discourse on “Lazy Nigerian Youths” conversations - Nkiru Comfort Ezeh; Augustine Godwin Mboso (Informasi, 2020)
The Social Media has emerged as a new platform for discourses. It has no doubt provided people with easier and faster accessibility to information and has become an outlet for them to share their views on socio-political issues. It has also been observed that negative and hate comments seem to dominate on social networks used for social and political communication. Anchored on Public Sphere Theory, focus group discussions were conducted with undergraduate youths in South-east Nigeria examined on the issue of President Mohammadu Buhari’s referring to Nigerian youths as lazy, while speaking at the Commonwealth Business Forum in Westminster on 18th April 2018. This article, therefore, explored the opinions advanced in the discourse based on the principles of freedom of expression and responsibility. The study suggests that while Twitter platform was more objective in the discussion of the issue of the day because it allows the use of filters to ensure that contents posted on the platform adhere strictly to rules and fair usage; Facebook and Whatsapp trailed with abuses and hate comments. The study recommended that owners of blogs and media houses who now post their contents on the social media should coordinate comments on such platforms and continue developing mechanisms that work to regulate the quality of posted content.